Acceleration and High-Speed Running Profiles of Women's International and Domestic Football Matches - Griffin, Jesse; Newans, Timothy; Horan, Sean; Keogh, Justin; Andreatta, Melissa; Minahan, Clare (Frontiers in Sports and Active Living, 2021)
Acceleration and deceleration are important given football is an intermittent sport with constant changes in velocity and direction. It is unclear, however, if the accelerations and decelerations performed by players differ between competition levels. The aim of the present study was to compare the acceleration, deceleration, and high-speed running profiles of players during international and domestic matches and to determine if differences were apparent across playing positions (defenders, midfielders, and attackers). GPS data from 21 Australian women’s domestic football league matches over 2 seasons (2016-2018) and 15 Australian women’s international matches (2017-2018) were collected and analysed. Movement pattern data was collected using VX Sport and GPSports 10 Hz GPS receivers. Variables analysed included: total distance, distance covered high-speed running (16-20 km∙h-1) distance covered sprinting (> 20 km∙h-1) and time spent accelerating and decelerating in four predetermined bands (1-2 m·s-2, 2-3 m·s-2, 3-4 m·s-2 and > 4 m·s-2). Results revealed that players competing in international matches covered significantly greater total distances, greater high-speed running distances and greater sprinting distances as well as spending a greater duration accelerating in band 4 compared to players in domestic competitions (p < 0.05). Players competing in international matches spent significantly less duration decelerating in bands 2 and 3, compared to players in domestic competitions. International defenders and midfielders recorded significantly higher total distances and high-speed running distance compared to players in domestic matches. Our findings suggest that preparing players for international-level competition should include progressive exposure to high-speed running and sprinting distances, as well as high magnitude accelerations. Furthermore, the higher running speeds experienced by players during international matches appears to be a result of less time spent decelerating. The optimal deceleration necessary for specific situations appears important and emphasises the need for specific deceleration training. The increased effort of high-intensity activity that is required for players competing in international matches affects defenders and midfielders to the greatest degree. Gradual exposure to the increased running demands for midfielders and defenders competing in international matches is needed to improve performance and reduce the potential risk of injury.